Martabat Manusia dalam Mahabarata Episode Pandhawa Dhadhu - YB. Rahno Triyogo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2023)
The dice game episode in the Mahabarata epic, in the Javanese wayang tradition, is known as lakon Pandhawa Dhadhu. It is called that because the tool used is called ‘dhadhu’. This episode tells the story of gambling between the Pandhawa and the Kurawa which had an impact on the erosion of human dignity at the lowest level. This happens because as the betting items are not only worldly possessions, but also human gamblers. It is said that in this game the Pandhawa always lost so that their wealth ran out. Because of his uncontrolled lust, Puntadewa placed his four brothers and himself at stake, as did Draupadi. The game ends when the Pandhawa have nothing to bet on. As a result of their defeat, they had to accept the consequences of becoming Kurawa slaves. The peak of tension occurred when Dushasana dragged Draupadi by grabbing her hair and pulling the cloth covering her private parts to strip her naked. In this episode, the treatment occurred beyond the limits of human values, which resulted in the abuse of human dignity. This article was written in order to provide a reaction to an extraordinary story that touches the deepest human values, namely the value of humans as a noble creation. Its glory should be maintained, cared for and developed so that it becomes more dignified, but what happens is just the opposite. Appreciation of this dice game episode is carried out based on moral values and cultural values that have been upheld since the beginning, namely the value of humans as noble creatures because they are equipped with reason, thoughts, conscience and feelings. The steps taken to produce a good article are to pay close attention to the development of the conflict plot which of course gives rise to tensions experienced by the story actors which ultimately have an impact on the reader or audience.